Cardiovascular risk stratification in elderly men with coronary heart disease - E. G. Volkova; I. V. Tantsyreva (Кардиоваскулярная терапия и профилактика)
Aim. To assess cardiovascular risk in elderly patients with coronary heart disease (CHD), in regard to myocardial structure and function, myocardial electrical activity, myocardial repolarisation heterogeneity, metabolic, immune and traditional risk factors (RFs).Material and methods. In total, 526 people aged 18-92 years were examined, including 167 elderly men with CHD (mean age 75,4 years) as the main group (MG), and 113 healthy men aged 18-65 years as the control group (CG). The MG participants were followed up for 10 years; CHD clinical course and fatal outcomes were monitored. The examination included the assessment of lipid profile (LP), apolipoprotein metabolism, coagulation and acute phase reaction parameters, humoral and cell immunity factors, myocardial electrical activity, ventricular activation velocity, myocardial electrical remodelling, repolarization parameters and their dispersion, as well as myocardial structure and function according to two-dimension echocardiography data.Results. In univariate analysis, significant predictors of cardiovascular death among the MG patients during 10-year follow-up period were: arterial hypertension (AH), low physical activity, high-density lipoprotein (HDL), apoAI, and apoB cholesterol (CH); increased left ventricular (LV) end-systolic and end-diastolic volume; increased LV myocardial mass; eccentric myocardial remodelling; reduced ejection fraction; terminal stage of electrical myocardial remodelling; increased QLend dispersion; increased blood phagocyte activity. In the MG individuals, the 10-year risk of cardiovascular death was significantly predicted by AH, chronic heart failure functional class, HDL-CH, QLend dispersion and terminal stage of myocardial electrical remodelling.Conclusion. In elderly CHD male patients, high-risk factors included AH, heart failure, HDL-CH, QLend dispersion and terminal stage of myocardial electrical remodelling. These factors should be considered in risk stratification while predicting 10-year cardiovascular risk.